The impact of Renewable Portfolio Standards on carbon emission trading under the background of China’s electricity marketization reform - Ying, Zhou; Xin-gang, Zhao (Energy (Oxford), 2021)
Carbon emission trading (CET) is an important mechanism for China to achieve carbon emission reduction targets and sustainable development. The success of its implementation depends on the scientific institutional supply design. At present, China is actively promoting the implementation of electricity marketization reform and Renewable Portfolio Standards (RPS), which would change the institutional environment for manufacturers’ decision-making and trading, thus impacting CET. Accordingly, this paper aims to establish an evaluation model using the system dynamics method to simulate and evaluate the impact of RPS on CET under the background of electricity marketization reform by designing and combining different policy scenarios. The results show that: (1) The impact of electricity marketization reform and RPS on carbon trading is mainly reflected in carbon emission rights’ demand, trading volume, trading price and power generation of manufacturers. (2) Under the situation of marketed electricity price and the absence of RPS, various indicators of the CET market are superior to other policy combinations. (3) Marketed electricity price can effectively stimulate manufacturers’ demand for carbon emission rights, increase trading volume, and have a positive impact on CET. However, the implementation of RPS weakens the demand for emission rights, reduces manufacturers’ power generation and profit, and harms CET. •Studied the impact of RPS on CET in the context of electricity marketization reform.•Establish an evaluation model by using the SD method.•Marketed electricity price positively affect CET, while the RPS harms CET.•The policy combination of marketed electricity price without RPS is optimal.